Climacteric Nature of the Carambola (A verrhoa carambola L.) Fruit. - Lam, P.F; Wan, C.K (1983)
The carambola (Averrhoa carambola L.) is determined to be a non-climacteric type fruit. The characteristic upsurge of carbon dioxide exhibited by climacteric fruits during the ripening process was not evident in carambola fruits of differing maturity. The ethrel treated fruit showed no sudden sharp increase in carbon-dioxide nor an ethylene peak.